2020
DOI: 10.3389/fpsyg.2020.568907
|View full text |Cite
|
Sign up to set email alerts
|

Extraversion Moderates the Relationship Between the Stringency of COVID-19 Protective Measures and Depressive Symptoms

Abstract: From the start of the COVID-19 pandemic, psychologists are theorizing that, as compared to introverts, extraverts experience more profound negative social consequences from protective measures (e.g., travel restrictions and bans on public gatherings). As the empirical evidence for this claim is lacking, this study tested the hypothesis that extraversion moderates the relationship between the stringency of COVID-19 protective measures and depressive symptoms. Our results were based on survey data from 93,125 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 40 publications
(69 reference statements)
6
41
0
2
Order By: Relevance
“…It is important to point out that these effects were observed when controlling for other Big Five traits (i.e., conscientiousness, agreeableness, openness). Overall, these results are consistent with the differential reactivity model of personality and stress (Bolger & Zuckerman, 1995) and recent findings in the context of the COVID-19 pandemic, suggesting that both extraversion (Nikčević et al, 2020;Wijngaards et al, 2020) and emotional stability (Kocjan et al, 2020;Kroencke et al, 2020;Lee & Crunk, 2020;Liu et al, 2020;Pradhan et al, 2020) relate to general levels of perceived stress, mental health, and subjective wellbeing during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It is important to point out that these effects were observed when controlling for other Big Five traits (i.e., conscientiousness, agreeableness, openness). Overall, these results are consistent with the differential reactivity model of personality and stress (Bolger & Zuckerman, 1995) and recent findings in the context of the COVID-19 pandemic, suggesting that both extraversion (Nikčević et al, 2020;Wijngaards et al, 2020) and emotional stability (Kocjan et al, 2020;Kroencke et al, 2020;Lee & Crunk, 2020;Liu et al, 2020;Pradhan et al, 2020) relate to general levels of perceived stress, mental health, and subjective wellbeing during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 88%
“…participants from 47 countries found that the stringency of protective measures (e.g., travel restrictions, ban of public events) during the early stages of the COVID-19 pandemic (i.e., end of March to early April 2020) was associated with fewer depressive symptoms among less extraverted people, whereas there was no significant relationship among more extraverted people (Wijngaards et al, 2020). Another cross-sectional study found that extraversion was negatively related to health-and COVID-19-related anxiety and, in turn, depressive symptoms and generalized anxiety (Nikčević et al, 2020).…”
Section: The Role Of Extraversion and Emotional Stabilitymentioning
confidence: 99%
“…It can be assumed that this subgroup of outgoing young people is characterized by high sensation-seeking, and that the lack of sensation causes distressing boredom. This idea is supported by research which found that the COVID-19 measures feel more unnatural for extravert people, leading to higher decreases in mental wellbeing and social connectedness as compared to introvert people (46,47).…”
Section: Discussionmentioning
confidence: 88%
“…One group of researchers claim that the lifestyle associated with social distancing during the pandemic might feel more unusual to extroverts than to people who score lower in extroversion, as individuals who score higher in extroversion trait are energized by crowds and social interactions, and seek the company of others when stressed [ 48 ]. Therefore, social isolation by inhibiting their need for social engagement might have more deleterious effects on the mental health of individuals who score higher in extroversion compared to people who score lower in extroversion, who continue to enjoy spending time in their solitude like the time before social distancing [ 49 ]. Many articles published on widely-visited popular websites such as Bloomberg (2020), Reuters (2020), The Conversation (2020) and the psychology website Psychology Today (2020) have introduced introversion as an asset for flourishing during social isolation related to COVID-19 [ 50 – 53 ].…”
Section: Introductionmentioning
confidence: 99%